Competency Levels of Construction Technology Lecturers and Their Implementation of Outcome Based Continuous Assessment in Malaysian Vocational Colleges - Jumantirah Mohd Alias; Yunus, Faizal Amin Nur (Online Journal for TVET Practitioners, 2026)
The implementation of continuous assessment in Malaysia’s Technical and Vocational Education and Training (TVET) system continues to show varied practices and misalignment with the core principles of Outcome Based Education (OBE), despite its mandate as an institutional requirement. Previous studies have highlighted that many lecturers face challenges in translating theoretical knowledge into authentic learning outcome based assessments. However, there remains a lack of empirical studies that systematically evaluate lecturers’ competency in implementing continuous assessment based on OBE, particularly in the context of the Construction Technology program in Vocational Colleges. Therefore, this study aims to examine the competency levels of Construction Technology lecturers in implementing continuous assessment based on OBE at Malaysian Vocational Colleges. The study focuses on three core competency constructs namely knowledge, skills and attitude, and investigates the relationship between competency levels and teaching experience. This quantitative survey involved a questionnaire administered to 151 lecturers from 44 Vocational Colleges across five main zones in Malaysia. Data were analysed using SPSS version 27, incorporating descriptive statistics (percentage, mean) and inferential analysis (Pearson Correlation). Findings revealed that knowledge (M = 4.14) and attitude (M = 4.49) levels were high, while skill levels were moderately high (M = 3.86). The correlation analysis also indicated a statistically significant but very weak relationship between teaching experience and competency level (r = 0.163), suggesting that experience alone does not guarantee proficiency in OBE based assessment practices. This study contributes to the enhancement of competency theory in the TVET context by proposing the development of contextual and hands-on assessment modules. The implications of this study support the development of a community of practice among educators, the strengthening of professional training strategies and the refinement of institutional competency monitoring policies.